ANALYSIS OF BATTERY ENDURANCE OF GT-VP 1500 WATT ELECTRIC MOTORBIKE - Novanto, Fahmi setia; Irawan, Hery (Institut Teknologi Adhi Tama Surabaya, 2025)
ABSTRACTThis research evaluates the efficiency of the KK Super Graphene battery in the GT-VP 1500-Watt electric motorcycle across both flat and inclined terrains. It begins with a literature review to gather relevant information, followed by material preparation, track selection, and an initial test of the electric motorcycle without current limitations on the 1500-watt BLDC motor. Test data were collected and analysed to compare performance differences between flat and inclined terrains. The study aims to assess the battery's efficiency under current limitations of the 1500-watt BLDC motor based on the findings. The test results for battery power consumption on flat terrain indicated a runtime of 14.75 hours at a speed of 15 km/h, 8.80 hours at 20 km/h, and 7.56 hours at 30 km/h. Meanwhile, the battery runtime on inclined terrain decreased to 8.08 hours at 15 km/h, 7.05 hours at 20 km/h, and 4.54 hours at 30 km/h. Keywords: electric motorbike battery, BLDC motor, speed